Impact of circuit configuration on the mechanical performance of CPAP therapy devices: an experimental study - De Luca, Margherita; Formaggio, Andrea; Terzini, Mara; Borrelli, Simone; Putame, Giovanni; Moretto, Francesca; Esposito, Teresa; Vaschetto, Rosanna; Morbiducci, Umberto; Olivieri, Carlo; Audenino, Alberto L. (Frontiers in Medical Technology, 2025)
IntroductionCPAP therapy treats various respiratory disorders. The overall performance of therapy delivery can be affected by the adopted circuit configuration. Recently, parallel to the canonical open configuration (OC), closed configurations (CC) have been proposed with potential advantages in terms of oxygen consumption, noise, airway dryness and contamination. However, the mechanical performance of CPAP devices in CC has been marginally investigated. The aim of this study is to clarify whether CPAP therapy delivered in CC configuration retains mechanical performances equivalent to that achieved in the canonical OC stipulated by the manufacturers.MethodsOCs and CCs implemented on seven different ventilation devices, classified as flowmeter, obstructive sleep apnoea device, and mechanical ventilator, were tested at different set CPAP levels. Mask and helmet interfaces were tested, and healthy, post-surgery and ARDS respiratory conditions were simulated. The mechanical performance was compared in terms of mean static pressure (Pmean), pressure oscillations, areas between pressure curve and Pmean during inspiration (Ai) and expiration (Ae), and the time in which the pressure curve remains above the Pmean along the expiration phase (T%).ResultsThe mechanical performances of CCs with helmet interface were comparable to canonical OCs used with mask interface. Globally, a CC supplied a reduced Pmean (on average, −1.3 cmH2O for the mask and −0.3 cmH2O for the helmet) and an increased ΔP, Ae and Ai (on average +0.5, +2.5, +2 times, respectively).ConclusionThe closed configuration proved its capability to effectively deliver CPAP therapy, thus making its intrinsic advantages available for future clinical use.